Krisis Sikap Profesionalisme Guru dalam Meningkatkan dan Memperkuat Karakter Siswa - Mahmuda Mahmuda (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The improvement of professional teachers had become a global focus both in level regional, Nasional, or International. Because teacher has a job and role vital is not only giving some knowledge information and technology, but also shaping attitude and soul who are able to hold out in hypercompetition era that where the era exist balance between cognitive and morality nation become unity as modernization era foundation. With the existing various of education problem who found as like disadvantages and advantages of teachers, the lack of human resources increase till implicit to the least establishment and improvement student character who has become a focus in the purpose this article so that it is necessary to do a research to get a more detail data in the respond about it because the professionalism attitude is very urgent, consequence it toward character building if it is not be responded exhaustively. Therefore it is necessary the existence some strategies to achieve target of professional teacher as follow: 1) giving education and training steeply toward teacher, 2) giving reward to master achievement, 3) the existence special attention toward teacher welfare both in financial or self motivation, 4) the necessary of communication and cooperation between stakeholders. Collectively the aspect is able to be solution in professionalism development along the growing problems and time.